2018
DOI: 10.3758/s13421-018-0845-1
|View full text |Cite
|
Sign up to set email alerts
|

Both attentional control and the ability to make remote associations aid spontaneous analogical transfer

Abstract: Given the widespread belief that analogical processing is an important mechanism for creative problem solving, despite the rarity of spontaneous transfer in laboratory studies, a critical direction for future research is to address which abilities may allow for the spontaneous analogizing between distant (superficially dissimilar) sources and targets. This study explores the role of individual differences in attentional control and the ability to make remote associations and their possible combined effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 69 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…The relational processing tasks included an analogical transfer problem (Gick & Holyoak, 1980), translating a statement into an algebraic expression (Martin & Bassok, 2005;Simon & Hayes, 1976), and a picture-mapping task (Markman & Gentner, 1993). These tasks, while heterogeneous in nature, were selected because they all involve some degree of relational reasoning and are used widely in the literature to study relational reasoning (e.g., Cushen & Wiley, 2018;Fisher, Borchert, & Bassok, 2011;Kubricht et al, 2017;Lewis & Mayer, 1987;Tohill & Holyoak, 2000;Vendetti, Wu, & Holyoak, 2014). Two of the selected tasks involve constructing an analogical mapping (the analogical transfer problem and the picture-mapping task), and all tasks involve consideration of relations between entities.…”
Section: Studymentioning
confidence: 99%
“…The relational processing tasks included an analogical transfer problem (Gick & Holyoak, 1980), translating a statement into an algebraic expression (Martin & Bassok, 2005;Simon & Hayes, 1976), and a picture-mapping task (Markman & Gentner, 1993). These tasks, while heterogeneous in nature, were selected because they all involve some degree of relational reasoning and are used widely in the literature to study relational reasoning (e.g., Cushen & Wiley, 2018;Fisher, Borchert, & Bassok, 2011;Kubricht et al, 2017;Lewis & Mayer, 1987;Tohill & Holyoak, 2000;Vendetti, Wu, & Holyoak, 2014). Two of the selected tasks involve constructing an analogical mapping (the analogical transfer problem and the picture-mapping task), and all tasks involve consideration of relations between entities.…”
Section: Studymentioning
confidence: 99%
“…Although there were no a priori predictions about the relative effectiveness of each study task at acquiring the target principle, any differences in study task performance between the different tasks would raise the concern that spontaneous transfer differences may be attributable to improved acquisition of the target principle instead of improved access. Such differences in study task performance would be problematic because prior work has found a relationship between how well participants can articulate the target principle during training and the likelihood of spontaneous transfer (Cushen & Wiley, 2018; Gick & Holyoak, 1983; Kubricht, Lu, & Holyoak, 2017). A linear regression model that predicted final study task performance with study task as a predictor was used to test for differences in the extent to which each study task encouraged acquisition of the target principle.…”
Section: Resultsmentioning
confidence: 99%
“…These findings could also help identify ways to facilitate performance on other problems that call for similar semantic processes as in RAT problem solving. For example, both RAT problems with remote answers and analogical transfer require the realisation of associations between remote concepts (Cushen & Wiley, 2018;Fu et al, 2013;Gick & Holyoak, 1980). RAT problems with close answers but having a large number of irrelevant associates are similar to other problem-solving domains where disregarding irrelevant information is critical, e.g., overcoming mental set and design fixation (Jansson & Smith, 1991;Viswanathan & Linsey, 2011;Wiley, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…RAT problems have been designed to assess individuals' ability to retrieve remote associates, which is considered to be critical in creative thinking (Mednick, 1962). Positive correlations have been reported between performance on RAT problem-solving and other creative problem-solving tasks, such as associative fluency (Levin, 1978;Mednick et al, 1964), rebus (MacGregor & Cunningham, 2008), verbal insight problem and analogical transfer (Ansburg & Dominowski, 2000;Cushen & Wiley, 2018). RAT problem solving is also viewed as a measure of convergent creative thinking because it involves finding a single correct solution to a problem where there are usually multiple apparent initial pathways (Brophy, 1998;Hommel, 2012;Lee & Therriault, 2013).…”
Section: Rat Problem Solvingmentioning
confidence: 99%